Augmented Reality in Books: An Evaluation of Alan Turing Book - Adachi, Bruno Hideki; Gonzaga, Júlia Carlos; Fernandes, Paula Cintra; Silva, Saul Emanuel Delabrida; Bim, Silvia Amélia; Boss, Silvio Luiz Bragatto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Augmented reality technology has become popular due to its portability on smartphones and glasses. The literature presents studies on the efficiency of using augmented reality. Despite the demonstrated efficiency, books must be prepared to be recognized and provide interaction. This paper aims to assess whether a children’s book written without the purpose of using augmented reality can be identified by the leading augmented reality SDKs. As a case study, we chose the book Alan Turing: his machines and secrets because it is illustrated a fact that facilitates recognition. Our tests were on two of the main SDKs for augmented reality development currently found on the market. Although one of the SDKs demonstrated that approximately 76% of the book is recognizable, we have identified some human-computer interaction challenges and research opportunities discussed in this work.